Роль пения в жизни человека - Maltseva E. N. (Spring school marathon, 2016)
The article deals with the connection between singing and psycho-physiological state of people, as well as the reflection of this phenomenon in linguistic consciousness by means of the musical metaphor in English. Both the historical backgrounds of the problem and up-to-date researches have been taken into consideration.
Keywords: здоровье; пение; музыка; ритм; гармония; health; singing; Music; резонанс; музыкальная метафора; harmony; rhythm; resonance; musical metaphor